PENGARUH STRUKTUR MODAL, CURRENT RATIO, TOTAL ASSET TURNOVER, PERTUMBUHAN PENJUALAN DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN. (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2015 sampai dengan 2017) - Deviana, 14.05.62.0018; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
The purpose of this study was to determine the effect of Capital Structure, Current Ratio, Total Asset Turnover, Sales Growth and Company Size on the Company's profitability proxied by Return On Assets (ROA) in manufacturing companies listed on the IDX. The population is manufacturing companies listing on the Indonesia Stock Exchange (BEI) in 2015-2017, namely 263 companies. The sampling technique uses purposive sampling. The results of the analysis concluded that: Capital structure does not affect the Company's profitability (ROA). Current ratio, Total Asset Turnover, Sales Growth and Company Size have a positive effect on the Company's profitability (ROA). Keywords: Capital structure, current ratio, total asset turnover, sales growth, firm size and profitability.